An Antioxidant and Sunscreen Activity of Bangkal Plants (Nauclea subdita) - -, Isnaini; Asnawati; Febriansyah, Febriansyah; Ulfah, Rahmaniah (Faculty of Medicine, Universitas Jember, 2025)
Skin cancer is the one of leading causes of illness and death worldwide. The World Health Organization (WHO) state that ultraviolet (UV) radiation can cause cancer because it damages cells and triggers tumour growth. Bangkal plants (Nauclea subdita (Korth) Steud) which grows widely in South Kalimantan, contain antioxidants such as flavonoids, phenolics, saponins and tannins. These compounds, found in the plant’s fruit and leaves, make Bangkal extract a potential natural sunscreen. This article aims to determine the antioxidant potential of the fruit and leaf extract through scavenging hydrogen peroxide, scavenging hydroxyl radicals and chelating metals activity tests and discover the sunscreen ability based on the sun protection factor (SPF). The extracts were tested at concentrations of 2.5, 5 , 10, 25 and 50 ppm. The study results show that the fruit extract exhibited the most substantial antioxidant activity potential in metal chelating and hydroxyl radical scavenging. Conversely, the bangkal leaf extract demonstrated greater activity in hydrogen peroxide scavenging than in chelating metal and hydroxyl radical scavenging. Based on the SPF value, bangkal leaf extract has greater sunscreen activity than the fruit extract, indicating its stronger potential for development into a sunscreen formula to help prevent skin cancer.